Global Financial Stability Report, April 2012 : The Quest for Lasting Stability. (Global Financial Stability Report; Global Financial Stability Report ;, 2012)
The April 2012 Global Financial Stability Report assesses changes in risks to financial stability over the past six months, focusing on sovereign vulnerabilities, risks stemming from private sector deleveraging, and assessing the continued resilience of emerging markets. The report probes the implications of recent reforms in the financial system for market perception of safe assets, and investigates the growing public and private costs of increased longevity risk from aging populations.